2014
DOI: 10.3390/ijms15046556
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Aldo-Keto Reductase Family 1 Member B10 in the Early Stages of Human Hepatocarcinogenesis

Abstract: Aldo-keto reductase family 1, member B10 (AKR1B10), a cancer-related oxidoreductase, is expressed in well-differentiated hepatocellular carcinomas (HCCs). However, AKR1B10 levels are minimal in normal liver tissues (NLs), similar to the 70-kilodalton heat shock protein (HSP70) and glypican-3. Moreover, the role of AKR1B10 in chronic hepatitis or cirrhosis, which are considered preneoplastic conditions for HCC, has not been fully elucidated. The aim of this study was to evaluate the expression of AKR1B10, HSP70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 37 publications
(47 reference statements)
3
28
0
Order By: Relevance
“…Consistent with previous findings [1][2][3], we found that ARK1B10 is over expressed in various liver cancer cells like HepG2, BEL-7402, and PLC; however, cholangiocarcinoma RBE cells displayed more AKR1B10 protein than any of the liver cancer cells listed above. The questions of whether or not it existed in cholangiocarcinoma tissue sample and the clinical significance of ARK1B10 over-expression in cholangiocarcinoma are not answered in this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous findings [1][2][3], we found that ARK1B10 is over expressed in various liver cancer cells like HepG2, BEL-7402, and PLC; however, cholangiocarcinoma RBE cells displayed more AKR1B10 protein than any of the liver cancer cells listed above. The questions of whether or not it existed in cholangiocarcinoma tissue sample and the clinical significance of ARK1B10 over-expression in cholangiocarcinoma are not answered in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The expression of AKR1B10, detected by Immunohistochemical analysis, is highest in HCC, then in non-tumorous liver tissues, and lowest in normal liver tissues with 54.8%, 2.1%, and 0.3% positive expression, respectively [3].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…As shown by Zhang et al (22), AKR1B10 promotes pancreatic carcinogenesis via modulation of the K-RAS/E-cadherin pathway. Several studies demonstrated AKR1B10 expression in HCC via immunohistochemistry (23)(24)(25)(26). To the best of our knowledge, however, there are no reports comparing AKR1B10 expression in HCC and CN tissue or determining its association with HCC prognosis.…”
Section: Discussionmentioning
confidence: 85%
“…While the function of NKX6.1 in gastrointestinal tumors, like HCC, have increasingly become the focus of attention in recent years. HCC is the fifth most common cancer and the third leading cause of cancer-related death worldwide [67][68][69] . The incidence of HCC has increased over serval years, but unfortunately, the long-term survival of HCC patients are still not ideal.…”
Section: Nkx61mentioning
confidence: 99%